2010
DOI: 10.2111/rem-d-09-00185.1
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Runoff Among Vegetation Patch Types: On Ecohydrological Optimality of Herbaceous Capture of Run-On

Abstract: A central tenant of ecohydrology in drylands is that runoff redistribution from bare to vegetated patches concentrates the key limiting resource of water, which can then enhance vegetation growth and biomass. Conversely, a reduction in vegetation patches, particularly those associated with herbaceous plants, can lead to a threshold-like response in which bare patches become highly interconnected, triggering a large increase in hillslope runoff and associated erosion. However, generally lacking is an assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 52 publications
1
43
0
2
Order By: Relevance
“…Puigdefábregas et al (1999) suggested that the ratio between sink and source areas in functional ecosystems remains within an optimum range that maximizes functionality. Urgeghe et al (2010) reported that the collection of runoff by herbaceous patches in a dryland pinyon-juniper ecosystem in southwest USA was maximum when both interpatch bare soil and herbaceous cover were intermediate, suggesting a trade-off between source and sink areas at the finer scale and the existence of herbaceous cover thresholds at the broader catchment scale. Some properties of the sink/source pattern, such as the upslope length and the size of the source area, have been successfully related to the performance of planted seedlings in drylands' restoration actions (Urgeghe and Bautista, 2015).…”
Section: Functional Approaches In the Monitoring Of Dryland Ecosystemmentioning
confidence: 99%
“…Puigdefábregas et al (1999) suggested that the ratio between sink and source areas in functional ecosystems remains within an optimum range that maximizes functionality. Urgeghe et al (2010) reported that the collection of runoff by herbaceous patches in a dryland pinyon-juniper ecosystem in southwest USA was maximum when both interpatch bare soil and herbaceous cover were intermediate, suggesting a trade-off between source and sink areas at the finer scale and the existence of herbaceous cover thresholds at the broader catchment scale. Some properties of the sink/source pattern, such as the upslope length and the size of the source area, have been successfully related to the performance of planted seedlings in drylands' restoration actions (Urgeghe and Bautista, 2015).…”
Section: Functional Approaches In the Monitoring Of Dryland Ecosystemmentioning
confidence: 99%
“…The same landscape with uniform disturbance may experience significantly more runoff and soil loss from a similar runoff event due to increased connectivity of bare soils and formation of well-organized concentrated flowpaths. These organized flowpaths rapidly accelerate runoff velocity and the ability of water to erode and transport sediment downslope (Davenport et al, 1998;Urgeghe, Breshears, Martens & Beeson, 2010;Wilcox, Davenport, Pitlick & Allen, 1996). Tongway, and Ludwig (1997) found for example that on degraded tussock grasslands, overland flow was concentrated in long straight paths between the grasses.…”
Section: Effects Of Vegetation Community Structure On Concentrated Flmentioning
confidence: 99%
“…The direction and intensity of water redistribution depend on a complex relation between vegetation attributes and soil properties, in combination with rainfall characteristics (e.g., event size or intensity; Cerda`1997, Davenport et al 1998, Puigdefabregas et al 1999. Runoff/runon redistribution can enhance NPP by concentrating water in vegetated patches, potentially reducing direct evaporation and increasing water available for plant transpiration (Bhark and Small 2003, Ludwig et al 2005, Urgeghe et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Two main challenges that livestock production faces in the region are the lack of fresh surface or groundwater sources for drinking supply, and the low fraction of the NPP that is allocated to forage (as opposed to non-forage woody tissues) in the rangelands (Baldi and Jobba´gy 2012). While the lack of fresh water is resolved by runoff harvesting in human-made impoundments (Magliano et al 2015b), the availability of forage here as well as elsewhere depends on the redistribution of surface water via runoff/runon to vegetation patches (Ludwig et al 2005, Urgeghe et al 2010. Both issues are highly dependent on horizontal water redistribution at the patch to landscape scales (Breshears et al 1997, Davenport et al 1998, and can be affected intentionally or non-intentionally by the management of livestock grazing and associated trampling and soil compaction (George et al 2004).…”
Section: Introductionmentioning
confidence: 99%